A framework in search of an optimal margining policy for official institutions: The Canadian experience - Tomo Nakashima; Mihai Cosma; Boran Plong (Bank of Canada, 2016)
One of the main outcomes of the global financial crisis has been a series of new regulations imposed on the financial system and specifically on banks. As a result of the changing regulations, bank dealers introduced various "credit" and "liquidity" charges for uncollateralized over-the-counter (OTC) derivatives trades, governed by a one-way or asymmetric credit support annex (CSA), whereby only bank dealers are required to post collateral in favour of official institutions - sovereigns, central banks, government agencies, sovereign wealth funds and supranational institutions - such as the Government of Canada. These charges have sharply increased costs for the government, which, like other official institutions, has been an extensive user of OTC derivatives. In this paper, we propose a framework that official institutions can use to analyze the cost and risk trade-offs among potential margining policies, including moving to a more symmetric CSA versus the prevailing one-way CSAs. Our analysis indicates that, in the case of Canada, moving to a more symmetric CSA results in lower cost and risk for the government relative to the prevailing one-way CSA margining policy, due to the government's relatively lower funding cost. In fact, all margining policies tested dominate the prevailing one-way CSA prior to 2015. As a result, remaining under the one-way CSA and continuing to transact OTC derivatives is no longer the best policy given the charges levied against the government.
Keywords: G32; 330; Foreign reserves management; Financial markets